THE SOCIAL STATUS OF WOMEN IN UZBEKISTAN DURING THE SOVIET PERIOD - Boltaeva Gulnoza Raxmatullaevna (American Journals Publishing, 2025)
This article analyzes the labor activity of Uzbek women during the Soviet period, the problems that arose in their everyday lives, the changes that occurred in their social life, as well as the positive and negative aspects of these processes.
Keywords: Social life, working hours, protection, labor, wages, leave, motherhood and childhood.